2019
DOI: 10.1093/mnrasl/slz122
|View full text |Cite
|
Sign up to set email alerts
|

Are there broad absorption-line blazars?

Abstract: We report the first systematic search for blazars among broad-absorption-line (BAL) quasars. This is based on our intranight optical monitoring of a well-defined sample of 10 candidates selected on the criteria of a flat spectrum and an abnormally high linear polarization at radio wavelengths. A small population of BAL blazars can be expected in the 'polar model' of BAL quasars. However, no such case is found, since none of our 30 monitoring sessions devoted to the 10 candidates yielded a positive detection of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Borguet & Hutsemékers (2010) simulated the two-component polar+equatorial wind model of quasar outflows and showed that it is necessary to include both the equatorial and the polar absorption regions to explain the C BAL profiles in some sources. However, the search of Mishra et al (2019) to find BAL blazars using intranight optical variability did not result in any detection. Interestingly, we find that the BAL fraction increases for the highest log(R 𝐼 ) (lowest orientation angles) bins even though the number of sources in these bins is low.…”
Section: Dependence Of Bal Fraction On Quasar Orientationmentioning
confidence: 90%
“…Borguet & Hutsemékers (2010) simulated the two-component polar+equatorial wind model of quasar outflows and showed that it is necessary to include both the equatorial and the polar absorption regions to explain the C BAL profiles in some sources. However, the search of Mishra et al (2019) to find BAL blazars using intranight optical variability did not result in any detection. Interestingly, we find that the BAL fraction increases for the highest log(R 𝐼 ) (lowest orientation angles) bins even though the number of sources in these bins is low.…”
Section: Dependence Of Bal Fraction On Quasar Orientationmentioning
confidence: 90%
“…The presence of INOV in the DLCs was checked by applying the test (de Diego 2010), following the basic procedure described in Mishra et al (2019). Among the 3 comparison stars initially chosen for a given session, we identified the steadier two by inspecting the star-star DLCs and the test was applied to only the 3 DLCs involving those two comparison stars and the target blazar.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, QSOs are used to study astrophysical problems in various fields. For instance, the spectrum of QSOs is a powerful tracer of the formation and evolution of black holes, the spins of black holes, and the co-evolution of black holes and host galaxies (Kormendy & Richstone 1995;Silk & Rees 1998;Kaspi et al 2000;Di Matteo et al 2005;Springel et al 2005;Kormendy & Ho 2013;Chen 2021;Valentini et al 2021); taking advantage of microlensing, astronomers study the feature of accretion disks with the light curves of QSOs (Agol & Krolik 1999;Morgan et al 2010;Dexter & Agol 2011;Blackburne et al 2011); the absorption lines of quasars are unique tracers of the interstellar media along the line of sight (Scaringi et al 2009;Hall et al 2013;Chen et al 2020;Mishra et al 2021;Zabl et al 2021). Besides, high-redshift quasars are valuable for understanding the reionization of the Universe and the formation of galaxies (McLure & Jarvis 2002;Wang et al 2019;Lupi et al 2021).…”
Section: Introductionmentioning
confidence: 99%